Ülevaade Ravimiameti 30. aastapäeva konverentsil „Ravimid, patsient ja innovatsioon“ käsitletud teemadest - Prii, Liis; Sulaoja, Stella; Tikk, Heili; Saar, Klara; Saar, Evelin; Suutre, Siim; Reinapae, Allan (Eesti Arst, 2021)
Eesti Arst 2021; 100(10):535–538